e^{-ax}γ(b,x)[0,∞]などの定積分

\begin{alignat}{2}
&(1)  \displaystyle\int_0^{\infty} e^{-ax}γ(b,x)dx=\frac{Γ(b)}{a(1+a)^b}\\
&(2)  \displaystyle\int_0^{\infty} e^{-ax}Γ(b,x)dx=\frac{Γ(b)}{a}\left\{1-\frac{1}{(1+a)^b}\right\}\\
\end{alignat}ただし、全て \(a,b \gt 0\)










<証明>

\((1)\) \(t=xr\) と置きます。\((dt=xdr)\)
\begin{alignat}{2}
\displaystyle\int_0^{\infty} e^{-ax}γ(b,x)dx&=\displaystyle\int_0^{\infty} e^{-ax}\left(\displaystyle\int_0^x t^{b-1}e^{-t}dt\right)dx\\
&=\displaystyle\int_0^{\infty} e^{-ax} \left\{\displaystyle\int_0^1 (xr)^{b-1}e^{-xr} \cdot xdr\right\}\\
&=\displaystyle\int_0^1 r^{b-1} \left\{\displaystyle\int_0^{\infty} x^be^{-(a+r)x}dx\right\}dr\\
\end{alignat}\((a+r)x=s\) と置きます。\([(a+r)dx=ds]\)
\begin{alignat}{2}
&=\displaystyle\int_0^1 r^{b-1} \left\{\displaystyle\int_0^{\infty} \left(\frac{s}{a+r}\right)^b e^{-s} \cdot \frac{1}{a+r}ds\right\}dr\\
&=\displaystyle\int_0^1 r^{b-1} \cdot \frac{1}{(a+r)^{b+1}}\left(\displaystyle\int_0^{\infty} s^b e^{-s}ds\right)dr\\
&=Γ(b+1) \displaystyle\int_0^1 \frac{r^{b-1}}{(a+r)^{b+1}}dr\\
\end{alignat}\(r=ay\) と置きます。\([dr=ady]\)$$=Γ(b+1) \displaystyle\int_0^{\frac{1}{a}} \frac{(ay)^{b-1}}{(a+ay)^{b+1}} \cdot ady=\frac{Γ(b+1)}{a} \displaystyle\int_0^{\frac{1}{a}} \frac{y^{b-1}}{(1+y)^{b+1}}dy$$\(\displaystyle y=\frac{1}{u}\) と置きます。\(\displaystyle \left(dy=-\frac{1}{u^2}du\right)\)
\begin{alignat}{2}
&=\frac{Γ(b+1)}{a} \displaystyle\int_{\infty}^a \frac{u^{1-b}}{\left(1+\frac{1}{u}\right)^{b+1}} \cdot \left(-\frac{1}{u^2}\right)du\\
&=-\frac{Γ(b+1)}{a} \displaystyle\int_{\infty}^a \frac{1}{(1+u)^{b+1}}du\\
&=-\frac{Γ(b+1)}{a}\left[-\frac{1}{b} \cdot \frac{1}{(1+u)^b}\right]_{\infty}^a\\
&=\frac{Γ(b+1)}{ab}\cdot \frac{1}{(1+a)^b}=\frac{Γ(b)}{a(1+a)^b}
\end{alignat}以上より$$\displaystyle\int_0^{\infty} e^{-ax}γ(b,x)dx=\frac{Γ(b)}{a(1+a)^b}$$








\((2)\) \(Γ(b,x)+γ(b,x)=Γ(b)\) であるので
\begin{alignat}{2}
\displaystyle\int_0^{\infty} e^{-ax}Γ(b,x)dx&=\displaystyle\int_0^{\infty} e^{-ax}\{Γ(b)-γ(b,x)\}dx\\
&=Γ(b)\displaystyle\int_0^{\infty} e^{-ax}dx-\displaystyle\int_0^{\infty} e^{-ax}γ(b,x)dx\\
&=Γ(b)\left[-\frac{e^{-ax}}{a}\right]_0^{\infty}-\frac{Γ(b)}{a(1+a)^b}\\
&=\frac{Γ(b)}{a}-\frac{Γ(b)}{a(1+a)^b}=\frac{Γ(b)}{a}\left\{1-\frac{1}{(1+a)^b}\right\}
\end{alignat}以上より$$\displaystyle\int_0^{\infty} e^{-ax}Γ(b,x)dx=\frac{Γ(b)}{a}\left\{1-\frac{1}{(1+a)^b}\right\}$$

コメントを残す

メールアドレスが公開されることはありません。 * が付いている欄は必須項目です